2019
DOI: 10.3390/polym11121929
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Redistribution for Enhancing Barrier Properties of Cellulose-Based Materials

Abstract: Renewable cellulose-based materials have gained increasing interest in food packaging because of its favorable biodegradability and biocompatibility, whereas the barrier properties of hydrophilic and porous fibers are inadequate for most applications. Exploration of lignin redistribution for enhancing barrier properties of paper packaging material was carried out in this work. The redistribution of nanolized alkali lignin on paper surface showed excellent water, grease, and water vapor barrier. It provided per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…It is worth mentioning that lignin content in the copolymers affects the air permeability and it could be used to control the air resistance of paper. These results are consistent with SEM results and agree with the data reported in the literature [38,39].…”
Section: Air Permeability Analysis and Thermal Stability Analysissupporting
confidence: 93%
“…It is worth mentioning that lignin content in the copolymers affects the air permeability and it could be used to control the air resistance of paper. These results are consistent with SEM results and agree with the data reported in the literature [38,39].…”
Section: Air Permeability Analysis and Thermal Stability Analysissupporting
confidence: 93%
“…We found that the oleophobic properties of the coated paper was significantly improved, and the surface of the MBP contained lignin 27 . Lignin redistribution on paper surface showed excellent grease barrier 28 . The exact reason is unknown but one hypothesis is that lignin has a lower surface energy compared to cellulose 29 .…”
Section: Rationalementioning
confidence: 98%
“…Lignin is the second-most abundant macromolecule group on earth, just after cellulose. It is a ubiquitous biopolymer found in the walls of plant cells, enabling their rigidity and imperviousness [1][2][3][4][5]. Its structure and concentration vary depending on the botanical source, age, and type of cell wall layers.…”
Section: Introductionmentioning
confidence: 99%
“…Narapakdeesakul et al [14] coated a linerboard using a twin-roll coating unit. The coating consists of lignin (1,3,5,7, and 9%) diluted in a coating medium. Water absorption of linerboards coated with lignin-based coatings was significantly lower than that of uncoated papers, with an optimum absorption for lignin content of 5%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation